O književni osebi in horizontu pričakovanj v predoperativnem in operativnem obdobju otrokovega bralnega razvoja - Kordigel Aberšek, Metka (Jezik in slovstvo, 2002)
The papers presnets the results of the second part if a study dealing with the child's receptive ability related to his mental scheme of the fairy-tale. The study was carries out at the Unit for Lower Primary School Education, Faculty of Education, University of Maribor. A qualitative analysis of the results of a productive creative process and an analysis of the results of a guided interview were performed to gain an insight into the child's horizon of expectations related to fairy tale characters, indirectly testing also the adequacy of the approximative literary-perceptive aims in the first and second triads of the nine-year primary education. These aims are related to perception, understanding and evaluation of the literary character in general(aims 4.1.1./4.2), and, more specifically, of fairy tale characters (aims 4.1.1./4.2)
Keywords: didactic method; didaktika; pouk književnosti; pravljica; fairy tale; branje; osnovne šole